PENGARUH CURRENT RATIO DAN TOTAL ASSETS TURNOVER TERHADAP RETURN ON INVESTMENT PADA PT HANJAYA MANDALA SAMPOERNA TBK PERIODE 2014-2023 - Hadi Rifai, Muhammad; Karolina (Journal of Research and Publication Innovation, 2024)
This study analyzes the influence of the Current Ratio and Total Assets Turnover on the Return On Investment (ROI) at PT Hanjaya Mandala Sampoerna Tbk from 2014 to 2023. Using a Descriptive Quantitative method, the research collects secondary data from the company's annual financial reports. The sample comprises 10 years of observations, from 2014 to 2023. Analytical techniques include multiple linear regression analysis using EViews 13, with tests such as the t-test for partial significance, the F-test for simultaneous significance, the R-squared test for model strength, and the Durbin-Watson test for autocorrelation detection. The study results show that the Current Ratio (X1) has a regression coefficient of 1.817357, a t-statistic of 2.544841, and a significance level of 0.0384, indicating a significant influence on ROI. Total Assets Turnover (X2) has a regression coefficient of 2453.625, a t-statistic of 4.958350, and a significance level of 0.0016, also showing a significant impact on ROI. The F-test reveals an F-statistic of 18.16557 with a significance level of 0.001695, indicating that both variables together significantly influence ROI. The R-squared value of 0.838453 means that 83.84% of the ROI variation is explained by the two independent variables. These findings support the hypothesis that the Current Ratio and Total Assets Turnover significantly affect ROI at PT Hanjaya Mandala Sampoerna Tbk.